Moral education of preschool children. - Ruziboeva Feruza Omonboevna (Euro Asian Journal Publishing, 2023)
This article explores the significance of moral education in the early years of a child's life, focusing on preschool children. The study delves into the existing literature on moral development, examines various methods employed in preschool settings, presents empirical results, and engages in a thorough discussion on the implications and potential for future research
Keywords: Moral education; preschool children; character development; values